The benefits and challenges of using crowdfunding to facilitate community-led projects in the context of digital civics. Issue 134 (February 2020) - Gooch, Daniel; Kelly, Ryan M.; Stiver, Alexandra; van der Linden, Janet; Petre, Marian; Richards, Mike; Klis-Davies, Anna; MacKinnon, Jessica; Macpherson, Robbie; Walton, Clare
Highlights: We present the first empirical investigation into the ability to crowdfund community-led projects in the context of digital civics. Working with four community projects we determine that crowdfunding can: Provide an alternative funding mechanism suitable for financing some community-led projects. Create a sense of empowerment and ownership. Increase community awareness. We identify and discuss four key challenges to using crowdfunding to support community-led projects, specifically: The time/benefit analysis. A reliance on existing social networks. The need for glamorous projects. Exclusiveness and marginalisation. We outline four key pieces of advice to community groups, namely: Lesson 1: Select your platform carefully. Lesson 2: Prepare your business model. Lesson 3: Work with other organisations. Lesson 4: Focus your messaging on benefits. Abstract: Digital technology is increasingly being used to bring citizens and communities together to address local concerns. While a variety of approaches have been developed that allow citizens and communities to improve their local communities, these approaches are often financially unsustainable. In this paper, we describe our exploration of crowdfunding as an alternative approach to funding community-led projects in the context of digital civics. Through our analysis of four community-led crowdfunding projects, we demonstrate that crowdfunding can a) provide an alternative funding mechanism suitable for financing community-led projects, b) create a sense of empowerment and ownership for project leaders, and c) increase community awareness of a project. By reflecting on our experiences, we identify four key challenges to utilising crowdfunding to support community-led projects in the context digital civics, namely 1) the benefits gained versus the time invested, 2) a reliance on existing social networks, 3) the need for glamorous projects and 4) issues of exclusiveness and marginalisation. We also provide advice specific to crowdfunding in the context of digital civics, before discussing the role of crowdfunding within digital civics. By addressing these challenges, we will be able to better support community groups crowdfund for the public good.